Public Compliance: Questioning Crisis Communication of Government During Covid-19 Pandemics - Jalaluddin Basyir; Rahmawati Haruna; Muh Sahran Almuhajirin (INJECT (Interdisciplinary Journal of Communication), 2021)
The persistence of the COVID-19 crisis has charged uncertainty and anxiety in public since March 2020. The government provides one of the strategic issues to respond to this crisis which is theology ritual so-called praying. However, public mostly do not respond to it. The data obtained from two news articles regarding to government's reaction in dealing with COVID-19 taken from tempo.co and Hans-Georg Gadamer hermeneutic method is used to analyse the data. The findings of this study indicate the symbol of theology ritual is not the crisis communication that should not be taken by government. It implicates that if the logic of text is reciprocal with the context of public, it subsequently has potential to be more accepted that means constructing public compliance.